Effects of non‐carious cervical lesion size, occlusal loading and restoration on biomechanical behaviour of premolar teeth. (December 2016) - Zeola, LF; Pereira, FA; Machado, AC; Reis, BR; Kaidonis, J; Xie, Z; Townsend, GC; Ranjitkar, S; Soares, PV
Abstract: Background: Information on fracture biomechanics has implications in materials research and clinical practice. The aim of this study was to analyse the influence of non‐carious cervical lesion (NCCL) size, restorative status and direction of occlusal loading on the biomechanical behaviour of mandibular premolars, using finite element analysis (FEA), strain gauge tests and fracture resistance tests. Methods: Ten buccal cusps were loaded on the outer and inner slopes to calculate the strain generated cervically. Data were collected for healthy teeth at baseline and progressively at three lesion depths (0.5 mm, 1.0 mm and 1.5 mm), followed by restoration with resin composite. The magnitude and distribution of von Mises stress and maximum principal stress were simulated at all stages using FEA, and fracture strength was also determined (n = 7 per group). Results: There were significant effects of the lesion size and loading directions on stress, strain and fracture resistance (p < 0.05). Fracture resistance values decreased with increase in lesion size, but returned to baseline with restorations. Conclusions: Combined assessment of computer‐based and experimental techniques provide an holistic approach to characterize the biomechanical behaviour of teeth with both unrestored and restored NCCLs.